Դիզայնը նախագծման գործընթացում - Լիլիթ Մելիքյան (ՀՀ ԳԱԱ հրատ.)
В статье представлены исторические особенности развития дизайна, которые охватывают все изменения окружающего мира, все творческие подходы, оказавшие непосредственное влияние на окружающую среду, природу, предметы. The article presents the characteristic features of the history of design development embracing every change in the world, every creative approach, which has direct influence on the transformations of the surrounding nature, environment and substance.
Keywords: Fine Arts; Architectural Drawing and Design